DAYA ANTIBAKTERI INFUSA BUAH MENGKUDU (MORINDA CITRIFOLIA,L) TERHADAP ESCHERICHIA DAN STAPHYLOCOCCUS AUREUS INVITRO - Rio Ferdian (Universitas Muhammadiyah Yogyakarta, 2003)
DAYA ANTIBAKTERI INFUSA BUAH MENGKUDU (MORINDA CITRIFOLIA,L) TERHADAP ESCHERICHIA DAN STAPHYLOCOCCUS AUREUS INVITRO